Domestic Violence and Sterilization Skew in India: An Instrumental Variable Analysis. Issue 3 (February 2022) - Patil, Vaishali Purushottam; Luck, Jeff; Yoon, Jangho; Khanna, Sunil
The objective of this study was to assess the prevalence of domestic violence in ever-married women in India and analyze the relationship between domestic violence and use of female sterilization as contraception. We analyzed data from the National Family Health Survey 2005–2006 (NFHS3). The Domestic Violence Module of the survey included abuse experiences and reproductive health outcomes of ever-married women aged 15 to 49 years ( n = 69, 704). The main outcome of interest was female sterilization and domestic violence experience was the main independent variable. Covariates in our multivariate regression models were guided by the socioecological model for domestic abuse. We estimated a reference linear probability model for the dichotomous outcome. We also employed an instrumental variables procedure to strengthen causal inference under such potential sources of bias as measurement error in reporting domestic violence and omitted variables. The reference model showed an increase of 2.1 percentage points ( p < .001) in the probability of female sterilization associated with exposure to domestic violence. After correcting the estimate for the measurement error and omitted variable bias, we found that domestic violence was associated with an increase in female sterilization by 6.4 percentage points ( p < .001), which is 18% higher than the rate of sterilization among non-victims. In conclusion, our findings imply that domestic violence may lead abuse victims to opt for female sterilization as contraception. Domestic violence is a significant obstacle to efficient contraceptive use. Programs directed toward violence prevention should work conjointly with family planning programs in India.